Multicenter study of endoscopic preoperative biliary drainage for malignant hilar biliary obstruction: E‐POD hilar study. Issue 5 (21st February 2018) - Nakai, Yousuke; Yamamoto, Ryuichi; Matsuyama, Masato; Sakai, Yuji; Takayama, Yukiko; Ushio, Jun; Ito, Yukiko; Kitamura, Katsuya; Ryozawa, Shomei; Imamura, Tsunao; Tsuchida, Kouhei; Hayama, Jo; et al.
Abstract: Background and Aim: Endoscopic nasobiliary drainage (ENBD) is often recommended in preoperative biliary drainage (PBD) for hilar malignant biliary obstruction (MBO), but endoscopic biliary stent (EBS) is also used in the clinical practice. We conducted this large‐scale multicenter study to compare ENBD and EBS in this setting. Methods: A total of 374 cases undergoing PBD including 281 ENBD and 76 EBS for hilar MBO in 29 centers were retrospectively studied. Results: Extrahepatic cholangiocarcinoma (ECC) accounted for 69.8% and Bismuth–Corlette classification was III or more in 58.8% of the study population. Endoscopic PBD was technically successful in 94.6%, and adverse event rate was 21.9%. The rate of post‐endoscopic retrograde cholangiopancreatography pancreatitis was 16.0%, and non‐endoscopic sphincterotomy was the only risk factor (odds ratio [OR] 2.51). Preoperative re‐intervention was performed in 61.5%: planned re‐interventions in 48.4% and unplanned re‐interventions in 31.0%. Percutaneous transhepatic biliary drainage was placed in 6.4% at the time of surgery. The risk factors for unplanned procedures were ECC (OR 2.64) and total bilirubin ≥ 10 mg/dL (OR 2.18). In surgically resected cases, prognostic factors were ECC (hazard ratio [HR] 0.57), predraiange magnetic resonance cholangiopancreatography (HR 1.62) and unplanned re‐interventions (HR 1.81). EBS was not associated with increased adverse events, unplanned re‐interventions, or a poor prognosis. Conclusions: Our retrospective analysis did not demonstrate the advantage of ENBD over EBS as the initial PBD for resectable hilar MBO. Although the technical success rate of endoscopic PBD was high, its re‐intervention rate was not negligible, and unplanned re‐intervention was associated with a poor prognosis in resected hilar MBO.